La ricerca applicata ai vini di qualità - Stefano Di Blasi (Strumenti per la didattica e la ricerca, 2012)
This is a book on the state of the art of scientific research applied to the fields of viticulture, management of the foliage, manual and mechanical harvesting, vinification techniques, the use of mixed yeast cultures, malolactic fermentation and microoxygenation. It synthetically illustrates the lines of research that the Consorzio Tuscania has co-ordinated in the four-year period 2007-2010. Each of these lines of research has been conducted in liaison with some of the most important scientific institutions in the sector: CNR Ibimet, DIPROVE (University of Milan), IASMA-FEM, University of Florence (DEISTAF, DIPSA, DIBA Departments), SAIFET (University-Polytechnic of the Marches) and DISAABA (University of Sassari). The work offer useful cues for updating the production techniques for quality red wines.